Polystyrene/sepiolites nanocomposite foams: Relationship between composition, particle dispersion, extensional rheology, and cellular structure. (December 2021) - Ballesteros, A.; Laguna-Gutierrez, E.; Puertas, M.L.; Esteban-Cubillo, A.; Santaren, J.; Rodriguez-Perez, M.A.
Abstract: The main objective of this work is to analyze how the cellular structure of foamed polystyrene based (PS) nanocomposites, produced by gas dissolution foaming, is affected by the extensional rheological behavior of the polymer matrix and by the dispersion degree of the particles. These composites have been produced with different types of natural and organomodified sepiolites and with different contents of these particles. The extensional behavior and the dispersion degree were characterized by extensional and shear dynamic rheology, respectively. The results obtained indicate that the extensional rheological behavior controls the foam degeneration mechanisms; meanwhile, the way in which the particles are dispersed in the PS matrix controls the nucleation mechanisms. Results also indicate that, in these systems, the characteristics of the cellular structure are mainly defined by the way in which nucleation occurs. Therefore, improving the dispersion degree is a key approach to reduce the cell size by 90%, with respect to the pure polymer. Graphical Abstract: ga1 Highlights: Blends of PS with natural and treated sepiolites have been produced. Extensional rheological properties and dispersion degree of PS/SEP was measured. Nanocomposite materials were foamed by the gas dissolution foaming process. Strong relationships founded between dispersion of sepiolites and cellular structure. Extensional Rheology determine the appearance of degeneration phenomena.